Acceptability and feasibility of insect consumption among pregnant women in Liberia. Issue 3 (1st March 2020) - Coley, Katrina M.; Perosky, Joseph E.; Nyanplu, Aloysius; Kofa, Alphonso; Anankware, Jacob P.; Moyer, Cheryl A.; Lori, Jody R.
Abstract: Maternity waiting homes (MWHs) in Liberia promote facility‐based delivery to reduce maternal mortality. However, women often must bring their own food and supplies to MWHs, which makes food insecurity a barrier to the utilisation of MWHs. Consumption of edible indigenous insects is a common practice and has notable nutritional benefits but has not been studied in Liberia as a potential solution to food insecurity at MWHs. The purpose of this study is to (a) examine the acceptability of insect consumption in the context of Liberian beliefs, (b) identify species commonly consumed by pregnant women in Liberia, and (c) examine the feasibility of harvesting insects as food and income generation for women staying at MWHs. Focus groups were conducted at 18 healthcare facilities in Liberia. Participants included chiefs, community leaders, women of reproductive age, traditional birth attendants, women staying at MWHs, and male partners. Focus group participants identified many different species of insects consumed by pregnant women in the community as well as the perceived health impacts of insect consumption. They also described their own experiences with insect hunting and consumption and the perceived marketability of insects, particularly palm weevil larvae. The results of these discussions demonstrate that insect consumption is an acceptable practice for pregnant women in rural Liberia. These findings suggest that it is feasible to further explore the use of palm weevil larvae as dietary supplementation and income generation for women staying at MWHs in Liberia.